Studi Kelayakan Lokasi Tempat Pembuangan Akhir (TPA) Sampah Di Distrik Oransbari Kabupaten Manokwari Selatan Berdasarkan Bebarapa Parameter Fisik - Ika Indrieaswati Ika Indrieaswati; Rosalina Rosina Mirino; Khristian Enggar Pamuji (FMIPA Universitas Papua, 2022)
This study was aimed to determine the feasibility level of the final disposal site (TPA) based on physical aspects in the Oransbari District according to SNI 19-3241-1994 and SNI 03-3241-1994. The method used is descriptive with field observation techniques. Measurement starts from the groundwater level using geoelectric mapping: Types of rock and distance to faults based on geological maps: slope, distance to rivers, distance to shoreline, and distance to airports based on topographic maps; rainfall data from BMKG; flooded and protected areas. Based on the results of the analysis of 10 physical parameters with the accumulated assessment (scoring) that has been done that the candidate for the location of the Final Disposal Site (TPA) is in the second interval class, with a score of 161, so that the feasibility value of the landfill location is included in the interval class 129 – 224. and categorized as “Required Enough”..